TINDAK TUTUR GURU SLB CAHAYA BANGSA PONTIANAK DALAM PROSES BELAJAR MENGAJAR: TINJAUAN PRAGMATIK - Ratih, Ratih; Muzammil, Ahmad Rabi?ul; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the teacher's speech acts used against children who have special needs in the teaching and learning process (SLB). The problems in this study are: (1) what types of speech acts are used by the Cahaya Bangsa Pontianak SLB teacher in the learning process. (2) what is the purpose of the speech act used by the SLB Cahaya Bangsa Pontianak teacher in the teaching and learning process. The purpose of this study was to explain the types of speech acts and action objectives used by SLB Cahaya Bangsa Pontianak teachers. This study used the referral method with qualitative research. Data is in the form of teacher's utterances to students, and student speech to the teacher. The data collection technique used is the skillful free listening technique (SLBC), video technique and note taking. The tools used are cameras and books. Based on the data analysis used speech acts locution, illocutionary, and perlokusi SLB Cahaya Bangsa Pontianak teacher in the teaching and learning process.Keywords: Speech Actions, SLB Teachers